On Cryptographic Information Security in Cloud Infrastructures: PKI and IBE Methods - Konstantin Grigorevich Kogos; Sergey Nikolaevich Kyazhin; Artem Vladimirovich Yuzbashev (Безопасность информационных технологий, 2014)
The application of cryptographic security methods in cloud infrastructure information security is analyzed. The cryptographic problems in cloudy infrastructures are chosen; the appropriate protocols are investigated; the appropriate mathematical problems are examined.